2015
DOI: 10.1002/acp.3092
|View full text |Cite
|
Sign up to set email alerts
|

Eye Remember What Happened: Eye‐Closure Improves Recall of Events but not Face Recognition

Abstract: Eye-closure improves event recall. We investigated whether eye-closure can also facilitate subsequent performance on lineup identification (Experiment 1) and face recognition tasks (Experiment 2). In Experiment 1, participants viewed a theft, recalled the event with eyes open or closed, mentally rehearsed the perpetrator's face with eyes open or closed, and viewed a target-present or target-absent lineup. Eye-closure improved event recall, but did not significantly affect lineup identification accuracy. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
(96 reference statements)
0
16
0
Order By: Relevance
“…What did the robber do next?) .Furthermore since 'eye closure', which refers to asking participants to close their eyes during a memory task, may sometimes enhance recall for event-related details (Vredeveldt, Hitch, & Baddeley, 2011;Vredeveldt et al, 2015) we also examined if CCR effectiveness would be enhanced when combined with additional witness-compatible open-ended questions and 'eye closure'. Thus, in this study, one of the groups of participants performed their second recall attempt using the CCR technique in conjunction with both these procedures (see method).…”
Section: Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…What did the robber do next?) .Furthermore since 'eye closure', which refers to asking participants to close their eyes during a memory task, may sometimes enhance recall for event-related details (Vredeveldt, Hitch, & Baddeley, 2011;Vredeveldt et al, 2015) we also examined if CCR effectiveness would be enhanced when combined with additional witness-compatible open-ended questions and 'eye closure'. Thus, in this study, one of the groups of participants performed their second recall attempt using the CCR technique in conjunction with both these procedures (see method).…”
Section: Current Studymentioning
confidence: 99%
“…However, it is essential to understand that the ECI comprises multiple mnemonics and instructions that can contribute differently to the ECI superiority effect (Griffiths & Milne, 2010). Thus several authors focused on assessing the efficacy of each individual component of the ECI, concluding that procedures such as establishing rapport (Vallano & Compo, 2015;Kieckhaefer, Vallano, & Compo, 2014), asking for an initial free report (Lamb, La Rooy, Malloy, & Katz, 2011), mental reinstatement of context (Memon & Bull, 1999) or 'eye closure' (Vredeveldt, Tredoux, Kempen, & Nortje, 2015) are often important techniques for obtaining more information.…”
Section: Introductionmentioning
confidence: 99%
“…If cannabis intoxication impairs recall of central details of the witnessed event (e.g., about perpetrators or weapons), that would be more problematic than if it impairs recall of peripheral details (e.g., about the surroundings). In the present study, we therefore distinguished between reported details pertaining to persons, actions, objects, and surroundings in the criminal event (for comparable coding procedures, see, e.g., Milne & Bull, ; Vredeveldt, Tredoux, Kempen, & Nortje, ). To our knowledge, no previous studies have examined this question.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows, however, that face recognition training programs are not effective (see e.g., Malpass, 1981; Malpass, Lavigueur, & Weldon, 1973;Woodhead, Baddeley, & Simmonds, 1979). Similarly, instructions that improve recall of events, such as mental context reinstatement and eye-closure, typically do not improve face recognition performance (e.g., Searcy, Bartlett, Memon, & Swanson, 2001; Smith & Vela, 1992;Vredeveldt, Tredoux, Kempen, & Nortje, 2015). In light of the fact that 1 Note that there is an important practical reason for this: many small offences, such as a parking offence or a broken bike light, would go unpunished if a single police statement were not sufficient evidence (see also Bleichrodt, 2015).…”
Section: Introductionmentioning
confidence: 99%